Influence of thermal ageing on tensile-plastic flow and work hardening parameters of Indian reduced activated ferritic martensitic steel (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
The present study investigates the influence of thermal ageing (873K/5000h) on the microstructure, tensile-plastic flow behavior, and work hardening parameters of normalized and tempered (N&T) 1.4W-0.06Ta Indian Reduced Activated Ferritic Martensitic (INRAFM) steel. To comprehensively understand the tensile-plastic flow response of the INRAFM steel across a broad temperature spectrum of 300-873 K, the Hollomon, Ludwigson and Voce equations were employed. The results reveal an augmentation in the strain hardening exponent following the ageing process, attributed to the heightened work hardening capability of the aged steel, while the strain hardening coefficient exhibited a decline post ageing. To elucidate the dislocation debris structure's formation and movement within both the N&T and thermally aged specimens, transmission electron microscopy (TEM) specimens were procured in close proximity to the tensile tested specimens at varying temperatures of 300, 573 and 873 K. The tensile plastic flow behavior at diverse temperatures was aptly described by Hollomon, Ludwigson, and Voce equations. The fitting accuracy of these equations was determined using the goodness of fit, as indicated by the lowest χ2 values. The constitutive Voce equation successfully captured the yield strength (YS) and ultimate tensile strength (UTS) with the initial stress and saturation stress acting as fitting parameters. Distinct patterns of initial stress and saturation stress variations were observed concerning both N&T and aged steel in relation to temperature. Furthermore, absolute value of the Voce strain component (nv) demonstrated a reduction consequent to ageing, manifesting a two-stage behavior corresponding to temperature elevation. Notably, the deceleration of the recovery process during high temperature conditions was more pronounced in the thermally aged steel when contrasted with the N&T steel. Conclusively, the Voce relation proved efficacious in predicting the yield stress (YS) and ultimate tensile strength (UTS) of both the thermally aged and N&T INRAFM steel at varying temperatures.
Keywords: Indian Reduced Activated Ferritic Martensitic steel; Thermal ageing; microscopy studies; Tensile-plastic flow behaviour; Ludwigson and Voce relation